Algorithm for Rapid Exclusion of Clinically Relevant Plasma Levels of Direct Oral Anticoagulants in Patients Using the DOAC Dipstick: An Expert Consensus Paper - Harenberg, Job; Gosselin, Robert C.; Cuker, Adam; Becattini, Cecilia; Pabinger, Ingrid; Poli, Sven; Weitz, Jeffrey; Ageno, Walter; Bauersachs, Rupert; Celap, Ivana; Choi, Philip; Douketis, James; Douxfils, Jonathan; Elalamy, Ismail; Falanga, Anna; Fareed, Jawed; Favaloro, Emmanuel J.; Gerotziafas, Grigorios; Herkner, Harald; Hetjens, Svetlana; Heubner, Lars; Klamroth, Robert; Langer, Forian; Lip, Gregory Y. H.; Mac Grory, Brian; Margetić, Sandra; Merrelaar, Anne; Pikta, Marika; Renne, Thomas; Schulman, Sam; Schwameis, Michael; Strbian, Daniel; Tafur, Alfonso; Vassart, Julie; Violi, Francesco; Walenga, Jeanine; Weiss, Christel (Thrombosis and Haemostasis, 2024)
With the widespread use of direct oral anticoagulants (DOACs), there is an urgent need for a rapid assay to exclude clinically relevant plasma levels. Accurate and rapid determination of DOAC levels would guide medical decision-making to (1) determine the potential contribution of the DOAC to spontaneous or trauma-induced hemorrhage; (2) identify appropriate candidates for reversal, or (3) optimize the timing of urgent surgery or intervention.The DOAC Dipstick test uses a disposable strip to identify factor Xa- or thrombin inhibitors in a urine sample. Based on the results of a systematic literature search followed by an analysis of a simple pooling of five retrieved clinical studies, the test strip has a high sensitivity and an acceptably high negative predictive value when compared with levels measured with liquid chromatography tandem mass spectrometry or calibrated chromogenic assays to reliably exclude plasma DOAC concentrations ≥30 ng/mL.Based on these data, a simple algorithm is proposed to enhance medical decision-making in acute care indications useful primarily in hospitals not having readily available quantitative tests and 24/7. This algorithm not only determines DOAC exposure but also differentiates between factor Xa and thrombin inhibitors to better guide clinical management.
Keywords: direct oral anticoagulants; point-of-care tests; urine; plasma; pooled analysis